Child Marriage Challenges and Institutional Countermeasures: Exploring Factors, Impacts, and Government Strategies in Islamic Context - Nabila Khoirunnisa Harliani; Elmahda Nabiilah (Saree: Research in Gender Studies, 2026)
Child marriage has shifted from a social phenomenon into a normalized community practice, creating a stark distinction and paradox with Islamic values that emphasize human welfare (maslahat al-ummah) and the protection of future generations (hifzh al-nasl). This practice also directly hinders the achievement of the Sustainable Development Goals (SDGs), particularly Gender Equality and No Poverty. This study aims to identify the driving factors of early marriage and analyze the strategic role of the regional government as the authorized guardian (ulil amri) in mitigating its negative impacts to build a resilient society. Using a descriptive qualitative approach, data were gathered through in-depth interviews with key stakeholders (Population control and family planning Office, public health Office, and the Office of Religious Affairs in Empat Lawang Regency), participatory observation, and focus group discussions. The findings indicate that the normalization of child marriage is driven by social constructs that view early marriage as an instant remedy for low educational attainment, poverty, lack of parental supervision, and out-of-wedlock pregnancies. There is a stark distinction between the community's cultural justification and true Islamic principles; public misinterprets early marriage as a moral shield, whereas Islam substantively warns against creating a "weak generation" (dzurriyyatan dhi'afan). The regional government’s role as the authorized guardian (ulil amri) in mitigating these impacts through reproductive health education and family assistance programs remains fragmented. The integration of religious institutions like the KUA in deconstructing this flawed understanding is not yet optimal. These findings imply that future policies must shift toward bottom-up community engagement and aggressive pre-marital counselling at the village level.   Abstract Indonesian Pernikahan anak telah bergeser dari sekadar fenomena sosial menjadi praktik masyarakat yang ternormalisasi, sehingga menciptakan distingsi dan paradoks yang tajam dengan nilai-nilai keislaman yang menekankan kemaslahatan umat (maslahat al-ummah) dan perlindungan generasi masa depan (hifzh al-nasl). Praktik ini juga secara langsung menghambat pencapaian SDGs, khususnya Gender Equality dan No Poverty. Oleh karena itu, penelitian ini bertujuan untuk mengidentifikasi faktor-faktor pendorong pernikahan dini dan menganalisis peran strategis pemerintah daerah sebagai pemimpin otoritatif (ulil amri) dalam memitigasi dampak negatifnya demi membangun masyarakat yang tangguh. Menggunakan pendekatan kualitatif deskriptif, data dihimpun melalui wawancara mendalam dengan pemangku kepentingan utama (DPPKB, Dinas Kesehatan, dan KUA di di Kabupaten Empat Lawang), observasi partisipatif, serta diskusi kelompok terpumpun. Hasil penelitian menunjukkan bahwa normalisasi pernikahan anak didorong oleh konstruksi sosial yang menganggap pernikahan dini sebagai solusi instan atas rendahnya tingkat pendidikan, kemiskinan, kurangnya pengawasan orang tua, dan kehamilan di luar nikah. Terdapat distingsi antara justifikasi kultural masyarakat dengan prinsip Islam yang sejati; masyarakat sering kali menyalahartikan pernikahan dini sebagai pelindung moral, padahal Islam memperingatkan agar kita tidak melahirkan "generasi yang lemah" (dzurriyyatan dhi'afan). Peran pemerintah daerah sebagai ulil amri dalam memitigasi dampak-dampak tersebut melalui edukasi kesehatan reproduksi dan program pendampingan keluarga masih terfragmentasi. Integrasi lembaga keagamaan seperti KUA dalam mendekonstruksi pemahaman keliru ini juga belum optimal. Temuan ini mengimplikasikan bahwa kebijakan di masa depan harus bergeser ke arah pelibatan masyarakat berbasis bottom-up (dari bawah ke atas) dan konseling pranikah yang agresif di tingkat desa.